2016
DOI: 10.1016/j.eplepsyres.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative prediction of temporal lobe epilepsy surgery outcome

Abstract: PURPOSE There is controversy about relative contributions of ictal scalp video EEG recording (vEEG), routine scalp outpatient interictal EEG (rEEG), intracranial EEG (iEEG) and MRI for predicting seizure-free outcomes after temporal lobectomy. We reviewed NIH experience to determine contributions at specific time points as well as long-term predictive value of standard pre-surgical investigations. METHODS Raw data was obtained via retrospective chart review of 151 patients. After exclusions, 118 remained (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…In agreement with our results, other studies have shown seizure free in the range of 60–70% after temporal lobectomy [ 21 , 22 , 23 ]. The proportion of patients free of seizure and aura over the long time in the current study (57.7%) was similar compared to a recent report that also showed complete seizure freedom in 65% of patients at 1year and in 56.5% at long-term follow-up of ≥5 years after temporal lobectomy [ 24 ]. Another author that included temporal and extratemporal resections detailed that >80% of the patients experienced class I outcome at the last four-year follow-up [ 25 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In agreement with our results, other studies have shown seizure free in the range of 60–70% after temporal lobectomy [ 21 , 22 , 23 ]. The proportion of patients free of seizure and aura over the long time in the current study (57.7%) was similar compared to a recent report that also showed complete seizure freedom in 65% of patients at 1year and in 56.5% at long-term follow-up of ≥5 years after temporal lobectomy [ 24 ]. Another author that included temporal and extratemporal resections detailed that >80% of the patients experienced class I outcome at the last four-year follow-up [ 25 ].…”
Section: Discussionsupporting
confidence: 87%
“…This pattern also anticipated a favorable clinical evolution five years postsurgery; and has been associated with good outcomes in patients with TLE in earlier studies [ 28 , 45 ]. Nowadays, the controversy about the relative contributions of ictal scalp VEEG, routine scalp outpatient interictal EEG, intracranial EEG and MRI for predicting seizure-free outcomes after temporal lobectomy still remains [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies have shown that surgery outcome varies over time and that the number of patients achieving seizure freedom decreases over several years ( 52 , 53 ). The estimation of surgery outcome at a different time point would likely have resulted in different groups and therefore possibly different results ( 54 ). Factors such as long-term tissue transformation or tumor growth can change surgery outcome at different time points ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…surgery. This will necessarily be dependent on the individual's clinical characteristics, imaging findings and interictal EEG abnormalities [30,31] A recent review concluded VEM findings failed to predict outcome at 6 months, 1 year and 2 years in temporal lobe epilepsy when corrected for routine EEG and MRI findings [32], and markers other than VEM findings, such as imaging may be more reliable in predicting postoperative seizure remission [33]. In pre-surgical planning VEM data must be reviewed in an epilepsy surgery MDT alongside all clinical information, imaging and neuropsychology.…”
Section: A View From the Cess (Children's Epilepsy Surgery Service)mentioning
confidence: 99%